Challenges of the Green Economy to the European Convention on Human Rights and the Charter of Fundamental Rights of the European Union - Juškevičiūtė-Vilienė, Agnė (Teisė, 2023)
-
Keywords: Green Economy; freedom of economic activity; environmental protection; European Convention on Human Rights; Charter of Fundamental Rights of the European Union; European Court of Human Rights; urisprudence of the Court of Justice of the European Union